Dual function mouse - Ahmad Muhddin Hidir, Othman (2015)
A computer mouse is an input device that is most often used with a personal computer. Moving a mouse along a flat surface can move the on-screen cursor to different items on the screen. Today, many computer mice use wired and wireless technology and have no wire. This Dual Function Mouse developed caused by problems faced by computer mice's users while using the existing device where, the wireless mouse's batteries run out of power accidently in the middle of their activities. Moreover, they need to stop their work or activities and spend money to buy new batteries. It will caused more money spend in a long term period. Besides that, wired mouse's users need to purchase a new wired mouse when the mouse's cable gets broken. Accordingly the problem statement, Dual Function Mouse developed to improve the quality and users performance in doing their activities such as doing work, playing computer games, and so on.